Study of Structural and Electrical Properties of Gallium Arsenide Thin Film Grown by MOCVD Using Trisdimethylamino Arsenic - I. Hamidah; N. Yuningsih; P. Arifin; M. Budiman; M. Barmawi (Indonesian Journal of Physics, 2004)
Trisdimethylamino Arsenic (TDMAAs) and trimethyl gallium (TMGa) have been successfully used as Arsenic (As) and gallium (Ga) precursors, respectively, for GaAs epitaxial layers growth by metal organic chemical vapor deposition (MOCVD) method. TDMAAs is used as As precursor due to its excellent properties, i.e. nontoxic, low carbon incorporation, low vapor pressure, and no need for precracking. The surface morphology of GaAs is observed by scanning electron microscopy (SEM) method and GaAs atomic fraction is measured by energy dispersive X-ray (EDX) method. From the examination of electrical properties by the standard Hall-van der Pauw measurement, it can be concluded that the film conductivity for all layers are p-type. GaAs with V/III ratio of 4.5 has a growth rate of 0.94 µm/h, mobility of 395 cm2/Vs and room temperature hole concentration of 3.44 x 1015 cm-3